Implementasi Asas Keadilan dan Kemanfaatan dalam Penetapan Konsinyasi Ganti Rugi Tanah Sengketa - Dama, Fatmawati; Wantu, Fence M; Achir, Nuvazria (PT. Meja Ilmiah Publikasi, 2025)
This study aims to answer how the principles of justice and benefit are implemented in determining compensation for disputed land in Decision No. 69/Pdt.P-Kons/2022/PN Gto. This study uses a normative legal method with a legislative approach and case study, where data is collected through literature review of regulations, court decisions, and relevant literature. The results of the study indicate that the judge granted the request for consignment based on Article 42(c) of Law No. 2 of 2012 due to the existence of a ownership dispute that prevented direct payment of compensation. The judge's ratio decidendi emphasized the principle of benefit to ensure the smooth progress of the dam construction project as a public interest, while also guaranteeing the rights of the parties by depositing the compensation funds with the court until the dispute is resolved. This ruling constitutes a legally valid and pragmatic solution to overcome land acquisition obstacles caused by disputes, but it raises a dilemma of timely justice for the entitled parties due to the delay in compensation rights is delayed until the ownership dispute is resolved. The impact of this study highlights the importance of strengthening technical guidelines for the implementation of consignment and accelerating the resolution of ownership disputes to achieve legal certainty and justice for all parties involved in land acquisition for public interest.